Abordagem da análise conjunta no processo decisório de aquisição do serviço de academia de ginástica - Campos, Lívia Maria Almendra Lemos Moerbeck de (2006)
The wellness, physical activity and health club market is in great expansion and grownth in the national and worldwide cenarium. In a growing competitive environment, the prediction of of consumer preferences over a product, for its innumerous attributes, is a critical aspect for any marketing administration. Determining customer perception of value in the form of utilities can provide the marketing administration of a company with a functional tool to evaluate the usefulness of a product or service. This thesis investigates the motivational attributes of decision making process when choosing a health club / gym center service. Data was collected through a web survey with 376 participants from Rio de Janeiro and Distrito Federal. The data was analysed through the conjoint analysis method. Results demonstrated that the relative values of the attribute regarding ¿gym facilities¿ and ¿attendance¿ obtained greater values than the other tested attributes. The ¿price¿ attribute was the third degree in the scale of value, followed by ¿proximity¿ and ¿indication¿.